Health related quality of life and manual ability 5 years after neonatal ischemic stroke. (September 2019) - Caspar-Teuscher, Miriam; Studer, Martina; Regényi, Maria; Steinlin, Maja; Grunt, Sebastian; ,
Abstract: Aim: To investigate health-related quality of life (HRQOL) and manual ability five years after neonatal arterial ischemic stroke (NAIS). Methods: Data was prospectively obtained by the Swiss Neuropaediatric Stroke Registry between 2000 and 2010. Two years after NAIS, cognitive and motor outcomes was assessed using the Bayley Scales of Infant Development (BSID-II). After 5 years, HRQOL was assessed with the KIDSCREEN-27 and manual ability with the ABILHAND-Kids. Manual ability and HRQOL were compared between children with and without cerebral palsy (CP) and HRQOL was correlated with manual ability. Results: Seventy-four patients were examined at the age of 2 years, at the age of 5 years 61 patients underwent a follow-up examination. Two years after NAIS, 29 children (39.1%) were diagnosed with CP. HRQOL 5 years after NAIS was comparable to normative values. Children with CP had a significantly lower HRQOL-index ( p = 0.013) and lower scores in the subscale psychological well-being ( p = 0.012 ) and social support & peers ( p = 0.048). The ABILHAND-Kids measure was significantly lower in children with CP compared to children without CP ( p < 0.001). Manual ability correlated significantly with HRQOL. Conclusion: Five years after NAIS, HRQOL is comparable to that of typically developing peers, but reduced in children with CP. Poorer manual ability is associated with lower HRQOL. Interventions improving hand function might influence HRQOL and should be considered early on. Highlights: HRQOL in NAIS survivors and typically developing peers is comparable. NAIS survivors with motor impairments have reduced HRQOL. Manual ability predicts HRQOL in NAIS survivors. Early assessment of manual abilities and timely interventions are crucial.